The effects of process variables on the hardness of nitrided 3% chromium steel - Mridha, Shahjahan; Khan, Ahsan Ali (Elsevier BV, 2008)
To achieve higher surface hardnesses with a steep hardness profile of the nitrided case is one of the main objectives of nitriding of commercial low-alloy steels. The effects of nitriding process variables and prior austenitizing and tempering temperatures have been investigated using En40B steels gas—nitrided at 470, 520 and 570 °C in different nitriding potentials for up to 96 h. The surface hardness was found to increase with increasing nitriding potential. The steeper hardness profiles and higher surface hardness were attained at the lower nitriding temperatures and higher nitriding potentials. With increasing nitriding temperatures, the surface hardness decreased and the hardness profile became shallower. The treatment time was found to have little effect on the surface hardness and the combined hardness curves obtained after different nitriding times gave the appearance of a hysteresis loop. The prior austenitizing temperatures appeared to have no influence on hardness. With increasing tempering temperatures the surface hardness of the nitrided case was observed to decrease and the hardness profile became shallower especially when nitrided at 570 °C. The decrease in surface hardness at higher nitriding temperatures is considered to be due to coarsening of the nitride particles, CrN, and the shallower hardness build up due to coarser alloy nitride precipitation which has actually transformed from large carbide particles formed during prior tempering at higher temperatures and in the carburized layer (CL).